Biometric IDs and the remaking of the Indian (welfare) state - Ursula Rao (economic sociology_the european electronic newsletter, 2019)
Across the globe, India's new digital identification system is celebrated as a brave attempt to revolutionise identification procedures. The new system launched in 2009 is called Aadhaar, which literally means "foundation".
Keywords: 300